SURGICAL MANAGEMENT OF CYSTIC LESIONS OF THE PANCREAS: A SINGLE-CENTRE EXPERIENCE - SIA,Gabriela Beatriz (2018)
ABSTRACT BACKGROUND: Cystic lesions of the pancreas represent a group of pancreatic diseases with great histological heterogeneity, varying from benign lesions, some of them with malignant potential, to overt malignant lesions. OBJECTIVE: To describe the cases of cystic lesions of the pancreas which underwent surgical intervention at a tertiary university hospital. METHODS: This is a retrospective population-based study (historical cohort) which was carried out enrolling individuals attended at the Outpatient service of Pancreas Surgery of the Hospital de Clínicas of Unicamp. The individuals underwent surgical procedures performed from January 2012 through December 2016. RESULTS: In the period evaluated, 39 cases of cystic lesions of the pancreas which underwent surgery were identified, 26 (66.6%) of which were female. The average age at diagnosis was 47.4±16.4 years (range, 18-73). In regards to symptoms, 35 (89.7%) were symptomatic. The average length of hospital stay was 10 days (range 4-76). Surgeries performed to treat the lesions depended on the localization and type of the lesions: cystojejunostomy (41%), distal pancreatectomy (36%), pancreaticoduodenectomy (15.4%), drainage of ruptured and/or infected pseudocyst (5.2%) and central pancreatectomy (2.6%). CONCLUSION: Cystic lesions of the pancreas are a group of lesions with a highly varying presentation and diagnostic approach and may require an also highly variable surgical treatment. An appropriate preoperative imaging diagnosis is essential for their management.